Mutation of TP53, translocation analysis and immunohistochemical expression of MYC, BCL-2 and BCL-6 in patients with DLBCL treated with R-CHOP. Issue 1 (December 2018) - Peroja, Pekka; Pedersen, Mette; Mantere, Tuomo; Nørgaard, Peter; Peltonen, Jenni; Haapasaari, Kirsi-Maria; Böhm, Jan; Jantunen, Esa; Turpeenniemi-Hujanen, Taina; Rapakko, Katrin; Karihtala, Peeter; Soini, Ylermi; et al.
Abstract Diffuse large B-cell lymphoma (DLBCL) is an aggressive lymphoma with diverse outcomes. Concurrent translocation ofMYC andBCL-2 and/orBCL-6, and concurrent immunohistochemical (IHC) high expression of MYC and BCL-2, have been linked to unfavorable treatment responses.TP53 -mutated DLBCL has also been linked to worse outcome. Our aim was to evaluate the aforementioned issues in a cohort of 155 patients uniformly treated with R-CHOP-like therapies. We performed direct sequencing ofTP53 exons 5, 6, 7 and 8 as well as fluorescencein-situ hybridization (FISH) ofMYC, BCL-2 andBCL-6, and IHC of MYC, BCL-2 and BCL-6. In multivariate analysis, TP53 mutations in L3 and loop-sheet helix (LSH) associated with a risk ratio (RR) of disease-specific survival (DSS) of 8.779 (p = 0.022) and a RR of disease-free survival (DFS) of 10.498 (p = 0.011). In IHC analysis BCL-2 overexpression was associated with inferior DFS (p = 0.002) and DSS (p = 0.002). DLBCL with BCL-2 and MYC overexpression conferred inferior survival in all patients (DSS, p = 0.038 and DFS, p = 0.011) and in patients with non-GC phenotype (DSS (p = 0.013) and DFS (p = 0.010). Our results imply that in DLBCL, the location ofTP53 mutations and IHC analysis of BCL-2 and MYC might have a role in the assessment of prognosis.